Leading by Example: Supervisor Modeling and Officer-Initiated Activities. (September 2015) - Johnson, Richard R.
The present study examined the effect of field supervisor behavior modeling on patrol officer use of unassigned patrol time. Specifically, the study explored whether field supervisor engagement in proactive stops and checks resulted in an increased frequency of proactive stops and checks among patrol officers. Hierarchical analyses of computer-aided dispatch data from two municipal police departments were conducted with 320 shifts and 1, 385 individual patrol officer tours of duty. After controlling for call for service workload, shift, agency, and officer demographic characteristics, the findings suggested that when field supervisors engage in proactive investigative activities, the volume of proactive activity by patrol officers approximately doubles. The policy implications and limitations of this study are then discussed.